The Digital Era of Hadith: Challenges of Authenticity and Opportunities for Innovation - Raidatul Umanah (IAIN Parepare, 2024)
The digital era has revolutionized how Muslims access hadiths, with applications and online platforms providing convenient access to vast collections. However, alongside these advancements, significant concerns have arisen regarding the validity of the content. Many platforms lack proper verification mechanisms, leading to the widespread dissemination of dhaif (weak) or maudhu' (fabricated) hadiths. This issue is exacerbated by low levels of hadith literacy among users, who often rely solely on search features without understanding the sanad (chain of narration) or matan (content), potentially distorting religious understanding and practices. This study explores the challenges and opportunities of digital hadith applications, focusing on content validity and the role of technology in hadith studies. Using a qualitative descriptive-analytical approach, data were gathered through library research, analyzing classical hadith collections, academic journals, and digital platforms. Case documentation was also utilized to identify examples of misinformation and evaluate digital platforms’ mechanisms for ensuring authenticity. The findings reveal that many digital applications fail to provide comprehensive sanad and matan verification, amplifying the risks of misinformation. However, technology offers substantial opportunities, including efficient access to primary sources, multilingual translations, and tools for interactive learning. These advancements highlight the potential for digital platforms to enhance hadith studies if developed responsibly. This study recommends collaborative efforts between scholars, developers, and educators to create reliable and authentic digital hadith platforms. Public education on the principles of hadith studies and responsible use of technology is crucial for preserving the integrity of Islamic teachings and ensuring their relevance in the digital age.